Supercooled plasma in high-power microwave discharges; Soviet Physics - Doklady; Vol. 32, № 1 - Didenko A. N. Andrei Nikolaevich; Petrov V. M.; Slinko V. N. Vladimir Nikolaevich; Sulakshin S. S.; Yushkov Y. G. Yuri Georgievich (1987, 1987)
В фонде НТБ ТПУ отсутствует